Examining the Impact of Motivation on Employee Performance: A Comprehensive Analysis of Influential Factors - Satoto, Eko Budi (Jurnal Ilmiah Manajemen & Bisnis, 2023)
Understanding the intricate factors influencing employee performance, encompassing the work environment, motivation, competencies, and compensation, is pivotal in effective human resource management. This comprehension aids companies in identifying areas for improvement, formulating robust human resource policies, fostering supportive work environments, and crafting compensation systems that optimally motivate employees, ensuring the organization's long-term success and sustainability. The primary objective of the study is a thorough investigation into the factors impacting employee performance, with motivation playing a key intermediary role. Employing a quantitative approach, the research utilizes Structural Equation Modelling (SEM) through Smart PLS version 3.0, focusing on personnel within the Public Relations Department of PT. XYZ. Findings reveal significant positive impacts of the work environment, competencies, and compensation on employee performance, with motivation exhibiting a significant negative influence. Interestingly, the study notes an insignificant negative impact of the work environment on motivation, contrasting with the positive effects of competencies and compensation on motivation. The study contributes theoretically by exploring motivation as an intervening factor in the real estate sector, offering practical insights for companies in the study location to make informed decisions about the work environment, competencies, compensation, and employee performance. Despite recognizing limitations, the study recommends future research to consider additional variables, enhancing the comprehensiveness of subsequent investigations.